Daily versus monthly reporting of post-traumatic symptoms: A study of reliability across time and instruments. Issue 2 (30th June 2015) - Westermeyer, Joseph; Shiroma, Paulo; Thuras, Paul; Kattar, Karen; Johnson, David; Crosby, Ross D.
Abstract: This study compared daily-versus-monthly self-ratings of post-traumatic symptoms using two similar but not wholly identical measures. The rationale was to determine whether (1) posttraumatic dissociation and/or minimization or (2) certain biases (more recent symptoms, more severe symptoms, practice effect, Hawthorne effect) might undermine symptom recall. Seventeen voluntary participants provided daily self-ratings for an average of 11.6 months. Nine male veterans had combat trauma; one also experienced sexual trauma. Four women had experienced sexual assault, and four women had other trauma. The monthly measure consisted of the self-rated Posttraumatic Stress Disorder (PTSD) Checklist (PCL), and daily ratings employed the self-rated PTSD Life Chart that we devised. These data revealed that people with Posttraumatic Stress Disorder (PTSD) produced monthly ratings that reflected their day-to-day symptom experience over the previous month, despite the dissociation and minimization that often accompanies PTSD. Initial practice effect occurred in the first month, but other biases (recent symptoms, severe symptoms, Hawthorne effect) were not demonstrated. Highlights: Monthly ratings showed high correlations with daily ratings. During the first month, practice effects occurred for all symptom clusters. Recent symptoms, highest symptoms, and RA meetings did not affect monthly ratings.